2014
DOI: 10.4049/jimmunol.1300514
|View full text |Cite
|
Sign up to set email alerts
|

JAK2-STAT3 Blockade by AG490 Suppresses Autoimmune Arthritis in Mice via Reciprocal Regulation of Regulatory T Cells and Th17 Cells

Abstract: IL-6–mediated STAT3 signaling is essential for Th17 differentiation and plays a central role in the pathogenesis of rheumatoid arthritis. To investigate the molecular mechanism underlying the antirheumatic effects and T cell regulatory effects of STAT3 inhibition, we studied the effects of the JAK 2 inhibitor AG490 on Th17 cell/regulatory T cell (Treg) balance and osteoclastogenesis. AG490 was administered to mice with collagen-induced arthritis (CIA) via i.p. injection, and its in vivo effects were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 47 publications
(43 reference statements)
1
59
0
Order By: Relevance
“…Small molecules targeting STAT3 have been demonstrated as potential pharmaceutical drugs for chronic joint inflammation and RA9101112. Previously, a DNA-binding site in the STAT3 core fragment was identified as a critical position for regulating STAT3 activity by small molecules2728.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small molecules targeting STAT3 have been demonstrated as potential pharmaceutical drugs for chronic joint inflammation and RA9101112. Previously, a DNA-binding site in the STAT3 core fragment was identified as a critical position for regulating STAT3 activity by small molecules2728.…”
Section: Discussionmentioning
confidence: 99%
“…For example, tofacitinib (an oral Janus kinase 3 [JAK3] tyrosine kinase inhibitor, Pfizer Inc.), which inhibits STAT3 phosphorylation, was approved by the US Food and Drug Administration (FDA) for the treatment of patients with RA who are unresponsive to disease-modifying antirheumatic drug (DMARD) therapy10. Further, recent studies showed that the non-peptide small molecules, STA-21 (STAT3 inhibitor) and AG490 (JAK2-STAT3 pathway inhibitor) improve the treatment efficacy considerably in active RA1112. Therefore, pharmaceutical approaches and advancements in STAT3-targeted small molecules have emerged as promising pharmacological therapies for RA.…”
mentioning
confidence: 99%
“…For the analysis of cell apoptosis, cells were stained with Annexin V and 7-AAD, and loaded on the flow cytometer. 12 Flow cytometric analysis was performed in a FACSCalibur instrument and analyzed with FlowJo software.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…The study by Yamauchi et al (104) revealed that pretreatment with the JAK2 inhibitor, AG-490 (108) reduced the functional recovery of hindlimbs after SCI, which indicated that activation of the JAK-STAT pathway induced by IL-6 in neurons may contribute to neuroprotection after SCI. As an effective trophic factor and pro-inflammatory factor, the LIF concentration increased within 24 h following SCI, indicating its vital role in regulating inflammatory reactions and preservation of oligodendrocyte following SCI (80,109). Although NGF and CNTF have diverse effects on the CNS, including differentiation and proliferation, they are able to enhance the survival of oligodendrocyte progenitors in CNS (110-117).…”
Section: Astrocyte-secretory Polypeptides Promote Neuroprotection Viamentioning
confidence: 99%